2023
DOI: 10.20945/2359-3997000000652
|View full text |Cite
|
Sign up to set email alerts
|

Association between sitagliptin plus vitamin D3 (VIDPP-4i) use and clinical remission in patients with new-onset type 1 diabetes: a retrospective case-control study

Marcelo Maia Pinheiro,
Felipe Moura Maia Pinheiro,
Marcelo Müller de Arruda
et al.

Abstract: Objective:The occurrence of partial remission (honeymoon phase) in type 1 diabetes (T1D) has been associated with a reduced risk of chronic microvascular complications of diabetes. We have published case reports showing that a combination therapy with the DPP-4 inhibitor sitagliptin plus vitamin D3 (VIDPP-4i) can prolong the honeymoon phase in patients with new-onset T1D. In the present case-control study, we investigated the frequency of occurrence of clinical remission (CR) in patients with new-onset T1D aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, among patients receiving ATG/G-CSF combination therapy, the most common worst-grade adverse events included lymphopenia (n = 15), decreased CD4 count (n = 15), hypoglycemia (n = 13), serum sickness (n = 13), and cytokine release syndrome (n = 11) [39] . Recently, promising results (in terms of prevention of T1D progression and preservation of endogenous insulin secretion) have also been observed from the off-label use of low-dose ATG in children aged 5-14 years with stage 2 T1D followed for 18-48 months [40] .…”
Section: Low-dose Atg Plus Pegylated G-csf Combination Therapymentioning
confidence: 99%
“…However, among patients receiving ATG/G-CSF combination therapy, the most common worst-grade adverse events included lymphopenia (n = 15), decreased CD4 count (n = 15), hypoglycemia (n = 13), serum sickness (n = 13), and cytokine release syndrome (n = 11) [39] . Recently, promising results (in terms of prevention of T1D progression and preservation of endogenous insulin secretion) have also been observed from the off-label use of low-dose ATG in children aged 5-14 years with stage 2 T1D followed for 18-48 months [40] .…”
Section: Low-dose Atg Plus Pegylated G-csf Combination Therapymentioning
confidence: 99%
“…This combination therapy has the potential to preserve β cell function in individuals with T1D ( 64 66 ). In a retrospective case-control study, it was observed that the combination of vitamin D plus DPP-4 inhibitors could notably prolong the honeymoon phase (partial remission of disease) in newly diagnosed T1D ( 50 ). However, further clinical trials are needed to confirm the potential role of this combination therapy in the onset and progression of T1D.…”
Section: Drug Combination Therapy For Diabetesmentioning
confidence: 99%
“…We believe that therapies aimed at interrupting the evolution of T1D should work together on the immune system and on the pancreatic islets ( 2 ). My group ( 3 ) and other authors have shown prolongation of the honeymoon phase and maintenance of C-peptide levels in T1D treated with dipeptidyl peptidase 4 inhibitors plus vitamin D3 (VIDPP-4i), with some patients not needing to be treated with insulin for up to 24 months. Promising results have been shown in NOD mice and humans treated with a combination of sitagliptin, γ-aminobutyric acid, and proton pump inhibitors, and some patients did not need to be treated with insulin for a long time ( 4 ).…”
mentioning
confidence: 99%